Refugio para poblaciones vulnerables víctimas de violencia en relación al género - Pizarro Velasquez, Diego (2020)
Gender-based violence, so often tolerated and legitimized within society, has historically taken various forms across a range of spheres and fields. Hence, in an attempt to mitigate and even eradicate this issue, a number of initiatives have emanated from different approaches to create measures that successfully result in new solutions. The research conducted for the purposes of this project seeks to make innovative contributions to the fight against gender-based violence, a phenomenon which infringes human dignity. With that in mind, this work offers new views and insights on the potential of architecture to enhance the psychological recovery process of victims of violence. Indeed, in conjunction with other specialized fields, such as psychology, psychiatry, sociology and Law, architecture can very well help victims to fully recover and return to a life a of dignity. The new approach herein proposed stresses the possible curative effects of architecture: by interacting within a newly designed architectural space, victims gain a sense of togetherness, protection and belonging to their environment. Accordingly, based on international literature on related architectural projects, an architectural fitting-out guide was elaborated for this type of facilities in Peru, given the fact that very few regulations have been established by the Peruvian government and its constituent institutions on this matter. This project ultimately aims to generate sound information that brings to light the problems experienced by victims of gender-based violence, as well as to propose new work approaches that can be broadly applied to other initiatives focused on the same issue.